Efektivitas Multimidia Interaktif Terhadap Pembelajaran Matematika Siswa Kelas V SD Negeri 58 Lubuklinggau - Riduan Febriandi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aims to develop a product in the form of interactive multimedia material speed, distance and time for fifth grade elementary school students and to produce effective interactive multimedia. This research is a development research with a Four-D model development model with the steps a) the define stage (definition), b) the design stage (planning), c) the develop stage (development), d) the disseminate stage (deployment). The subjects in this study were fifth grade students of SD Negeri 58 Lubuklinggau. Based on the results of the research by doing the t test, to get the value of t count with degrees of freedom (dk) or an error level of 5%, where to get dk = n1 + n2 - 2. dk = 182 with α 5%, the value of ttable is 1.65. After the analysis is done, it is found that 4.94 > 1.65, or tcount > ttable, it can be concluded that Ha is accepted and Ho is rejected. From the results of this research, it can be concluded that the use of Interactive Multimedia learning media on the material of speed, distance and time meets the effective criteria and can be used by teachers and students in learning. Keywords: Effectiveness, Interactive Multimedia, Mathematics